Mourning the Ends: Collaborative Writing and Performance - Ambayec, Maria Shantelle Alexies; van Baarle, Kristof; Burke, Peter; Gaspar, Renata; Goudouna, Sozita; Ovalıoğlu Gros, Nilüfer; Hafez, Adham; Kühling, Jan-Tage; Laine, Eero; Lucie, Sarah; Martins Rodrigues de Moraes, Juliana; Moritz, Evan; et al. (punctum books, 2025)
Mourning the Ends: Collaborative Writing and Performance is an opening, a beginning, an attempt to rethink how we can be, think, and work together. This book, authored by a multitude, explores new methodologies of collaborative scholarship for the arts and humanities within the context of the various ecological, medical, military, and epistemic ends facing the world. The authors of Mourning the Ends performed an experimental methodology as the book was researched, written, and revised by fifteen individuals situated across the globe. The writing emerged in part from a shared sense of mourning through the global pandemic and ongoing ecological catastrophes, yet the questions and arguments that are raised are immediately relevant as the rolling crises of our contemporary moment play out and further develop. The volume challenges a number of key areas in performance studies as well as foundational expectations and assumptions of the arts and humanities more broadly—namely, that writing and scholarship should be solitary endeavors. The authors write back against the model of thinking and studying that centers the singular genius, especially against the backdrop of enduring and apparent end times. Mourning the Ends is in some ways a rehearsal for another future, a speculative engagement with performance, ecology, and academic affiliation beyond institutional bounds—a methodology for shared mourning, performance, and thinking.